PENGARUH PEMBERIAN BEASISWA BANTUAN BELAJAR MAHASISWA (BBM) TERHADAP HASIL BELAJAR MAHASISWA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 339-347 , Roki Komanhar (Universitas Negeri Padang, 2014)
ABSTRACT Design of this research is causal comparative research that has goal to know about the effect of providing scholarship BBM toward students’ learning outcomes in the Faculty of Engineering State University of Padang. Research hypothesis is there is increasing of learning outcomes before and after receiving scholarship BBM. The population of this research all of the students in the Faculty of Engineering State University of Padang; include the students 2009 and 2010 who received BBM in the 2012 totally 177 of students. Technique of sampling is proportional random sampling and the number of samples is 74 students. Based on the result of data analysis by using Two Related Samples test, obtained value of significance is 0.104 > 0.05 so Ho is accepted or there are no increase learning outcomes of students after and before receive the scholarship BBM. It means that the hypothesis is rejected. The mean scores of IP whose students before receive scholarship BBM is 3.13 and after receive the scholarship BBM is 2.92. It can be said, after receiving scholarship BBM the mean scores of IP whose students are decreases. Based on explanation above, it can be conclude the effect of providing scholarship BBM have not been capable to increase students’ learning outcomes and so on the relation between learning outcomes of students and providing of scholarship BBM is not significance. Key word : providing, scholarship BBM, students’ learning outcomes